Answer:
![y=\sqrt{x+36}](https://tex.z-dn.net/?f=y%3D%5Csqrt%7Bx%2B36%7D)
Step-by-step explanation:
Since, for finding the inverse of a function f(x) we follow the following steps,
Step 1 : Replace f(x) by y,
Step 2 : Interchange x and y,
Step 3 : isolate y in the left side,
Step 4 : Replace y by ![f^{-1}(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29)
Given equation is,
![y=x^2-36](https://tex.z-dn.net/?f=y%3Dx%5E2-36)
Here, we do not need to apply step 1 and step 4,
Now, Interchange x and y,
![x=y^2-36](https://tex.z-dn.net/?f=x%3Dy%5E2-36)
![-y^2=-x-36](https://tex.z-dn.net/?f=-y%5E2%3D-x-36)
![y^2=x+36](https://tex.z-dn.net/?f=y%5E2%3Dx%2B36)
Taking square root both sides,
![y=\sqrt{x+36}](https://tex.z-dn.net/?f=y%3D%5Csqrt%7Bx%2B36%7D)
Which is the required equation of inverse of the given equation.